Momentum strategies in the Singapore equity market. - Tan, Ivan Chin Huat. (2008)
Research has found evidence that equity returns can be predicted with some reliability, particularly in the American and European markets. This study, however, finds that there is little evidence to support the prevalence of price momentum in Singapore market.